MODERN EDUCATIONAL TECHNOLOGIES AND PEDAGOGICAL INNOVATIONS AS A TOOL FOR EDUCATION QUALITY MANAGEMENT (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
The basis of educational quality management is the transition from teaching methods to the introduction of educational technologies into the educational process. The article discusses several definitions of educational technology.